The Influence of Board of Directors' Demographic Background on Carbon Emission Disclosure : An Empirical Study on Energy Sector Companies Listed on the Indonesia Stock Exchange in 2021–2023 - Luh Putu Citra Kusuma; I Nyoman Wijana Asmara Putra (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Carbon emission disclosure is a form of corporate concern aimed at maintaining emission levels below permitted thresholds through written disclosures in sustainability reports. One of the factors identified as influencing carbon emission disclosure is the demographic background of the board of directors, including age, nationality, and educational background. This study aims to examine the influence of the board of directors' demographic background on carbon emission disclosure. The population in this study consists of energy sector companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period. The sample was selected using a purposive sampling method, resulting in 117 observations. Learning theory serves as the theoretical basis for the analysis and interpretation of the findings. Data analysis was conducted using the Statistical Package for Social Sciences (SPSS) software. The results indicate that age, nationality, and education of the board of directors have a positive effect on carbon emission disclosure. The theoretical implication of this study is that demographic backgrounds of board members contribute to the adoption of environmental reporting practices. Practically, the findings are expected to provide useful information and considerations for companies, investors, and policymakers in decision-making processes.